Dairy cattle enteric methane measured in Brazilian tropical conditions - Primavesi, Odo; Frighetto, Rosa Toyoko Shiraishi; Pedreira, Márcio dos Santos; de Lima, Magda Aparecida; Berchielli, Telma Teresinha; Barbosa, Pedro Franklin (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to quantify methane (CH4) emission using the sulfur hexafluoride (SF6) tracer technique, by dairy cattle on pasture in Brazilian tropical field conditions. Measurements were performed in the rainy season, with Holstein and Holstein x Zebu crossbred, from lactating and dry cows and heifers grazing fertilized Tobiatã grass, and heifers grazing unfertilized Brachiaria grass. Methane and SF6 concentrations were determined by gas chromatograph. Methane emissions by lactating cows varied from 13.8 to 16.8 g/hour, by dry cows from 11.6 to 12.3 g/hour, by heifers grazing fertilized grass was 9.5 g/hour and by heifers grazing unfertilized grass varied from 7.6 to 8.3 g/hour or 66 to 72 kg/head/year. Methane emission per digestive dry matter intake (DMDI) varied from 42 to 69 g/kg DMDI for lactating cows, 46 to 56 g/kg for dry cows, 45 to 58 g/kg for heifers grazing fertilized grass and 58 to 62 g/kg for heifers in unfertilized grass pasture. The CH4 emission measured on dairy cattle feeding tropical grasses was higher than that observed for temperate climate conditions.